Frequency of Uveitis in the Central Tokyo Area (2010–2012). (24th August 2017) - Nakahara, Hisae; Kaburaki, Toshikatsu; Tanaka, Rie; Takamoto, Mitsuko; Ohtomo, Kazuyoshi; Karakawa, Ayako; Komae, Keiko; Okinaga, Kimiko; Matsuda, Junko; Fujino, Yujiro
ABSTRACT: Purpose : To investigate the frequency of conditions of newly arrived patients with uveitis from 2010 to 2012 and compare this frequency with that since 2004. Methods : We retrospectively analyzed clinical records of patients who visited the outpatient clinic from January 2010 to December 2012, and compared them with those from 2004–2009. Results : From 2010 to 2012, 695 new patients with uveitis visited Tokyo University Hospital, with a definite diagnosis made in 431 (62.0%). The most common diagnosis was scleritis (8.3%), followed by sarcoidosis (8.1%); herpetic iridocyclitis (5.5%); Behçet disease (4.6%); Vogt–Koyanagi–Harada disease (4.0%); acute anterior uveitis (3.7%); Posner–Schlossman syndrome (3.6%); intraocular malignant lymphoma (3.0%); and bacterial endophthalmitis (1.9%). The most frequent unclassified type of uveitis was sarcoidosis-suspected (14.8%). Conclusions : When compared with years 2004–2009, the present series showed an increasing trend of intraocular malignant lymphoma, bacterial endophthalmitis, and chronic iridocyclitis, and a notable increase in chronic iridocyclitis in young girls, with decreasing trends of scleritis and Vogt–Koyanagi–Harada disease.